2020
DOI: 10.1177/0022034520926139
|View full text |Cite
|
Sign up to set email alerts
|

Interdental Cleaning and Oral Health Status in an Adult Cohort, 2015 to 2018

Abstract: Interdental cleaning is routinely recommended, despite limited evidence supporting efficacy to prevent advanced oral disease endpoints, such as caries and periodontal disease. We aimed to examine associations between interdental cleaning and oral health in a large, generalizable prospective cohort of adults in the United States. Data were drawn from wave 3 (2015 to 2016, n = 26,086 included in analysis) and wave 4 (2016 to 2018, n = 22,585) of the adult component (age ≥18 y) of the nationally representative Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A recently published nationally representative longitudinal study revealed that frequent interdental cleaning is associated with better self-perceived oral health and less volume of gingival bleeding but less with measures of more advanced periodontal disease 10 . The proportion of participants who used interdental cleaners in NHANES from United States exceeded 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published nationally representative longitudinal study revealed that frequent interdental cleaning is associated with better self-perceived oral health and less volume of gingival bleeding but less with measures of more advanced periodontal disease 10 . The proportion of participants who used interdental cleaners in NHANES from United States exceeded 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent large-scale longitudinal study, interdental cleaning could alleviate self-reported gingivitis. However, its effectiveness in preventing advanced periodontitis has not been confirmed 10 . According to the study of Kim and Han, dental floss, but not interdental brushes, could prevent periodontal disease 8 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the Cochrane Review [ 8 ], DF or ICP in addition to toothbrushing may reduce gingivitis, biofilm formation, or both more efficiently than toothbrushing alone. In a cohort study conducted in the United States [ 30 ], interdental cleaning was associated with a reduction in self-reported gingivitis, and several epidemiological studies [ 14 , 29 ] have also reported that interdental cleaning and the use of DF and IDB among various ICPs could reduce gingivitis and biofilm. In this study, it was also confirmed that when interdental cleaning was performed using one or more DF or IDB, the gingivitis OR decreased to 0.721 (95% CI: 0.676–0.770) and periodontitis OR decreased to 0.642 (95% CI: 0.597–0.690).…”
Section: Discussionmentioning
confidence: 99%
“…9 The majority of epidemiological evidence supporting a positive association between ENDS use and adverse oral health comes from cross-sectional studies [10][11][12][13][14] ; longitudinal findings have been inconsistent. 15,16 Understanding health effects of tobacco use, particularly of noncigarette products, is one of the US Food and Drug Administration's (FDA) tobacco regulatory research priorities. 17 We examined associations between tobacco use and the incidence of adverse oral health outcomes (ie, gum bleeding, precancerous oral lesions, bone loss around teeth, bleeding after brushing or flossing, loose teeth, and 1 or more teeth removed) across different tobacco products among adults (aged Ն18 years) using data from the Population Assessment of Tobacco and Health (PATH) Study, a unique resource for longitudinal measures on tobacco use and oral health in a US nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%